Estimation Model On Newborn Anthropometry Based On Mid- Upper Arm Circumference (MUAC) - Ema Wahyu Ningrum; Etika Dewi Cahyaningrum (Universitas Aisyiyah Yogyakarta, 2020)
The measurement of MUAC is a way to identify the risk of chronic energy deficiency (CED). Pregnant women with CED are at risk of delivering Low Birth Weight Babies (LBW), short body length babies (stunting). The objective: to analyze the accuracy and estimation prediction of MUAC measurements on Newborn anthropometry. The Method: The design of this study is descriptive korelatiff, with a cross sectional approach. Quota sampling sampling techniques were 30 mothers and newborn babies. The data is secondary data taken from KIA book. Analysis using Spearman rank test and linear regression. Results: The accuracy measurement of MUAC for birth weight was 81.6% (r = 0.903, r2 = 0.816, p value = .0001). The accuracy measurement of MUAC for the birth length of a baby was 45.9% (r = 0.691, r2 = 0.459, p value = 0.0001). Estimation model for a baby’s birth wieght : -639,540+139,240* MUAC (cm), Estimation model for noewborn’s length : 37,566+0.409* MUAC (cm). The conclusions: Every 1 cm increase in MUAC there is a baby's birth weight gain of 139.240 grams. Each increase of 1 cm of MUAC there is addition of length of newborn baby 0.409 cm.